Evaluation of different fungicides and nitrogen rates on grain yield and bread-making quality in wheat affected by Septoria tritici blotch and yellow spot. (September 2018) - Castro, Ana Carolina; Fleitas, María Constanza; Schierenbeck, Matías; Gerard, Guillermo Sebastián; Simón, María Rosa
Abstract: This study aims to evaluate the influence of different fungicide mixtures under three nitrogen (N) fertilization rates on the area under disease progress curve (AUDPC) of STB (Septoria tritici blotch, Zymoseptoria tritici ) (hemibiotrophic) and YS (yellow spot, Pyrenophora tritici-repentis (Died) Drechs (anamorph Drechslera tritici-repentis (Died) Shoem) (necrotrophic) separately inoculated, green leaf area duration, and its effect on grain yield, grain protein concentration (GPC) and bread-making traits. Fungicide applications decreased AUDPC of both diseases compared to the control treatment, without significant differences between fungicide types. Fungicides increased green leaf area duration and grain yield compared to the control treatment, although no differences were found between fungicide types when STB was the prevalent disease. The GPC was increased by STB and YS, whereas fungicides decreased it. Those reductions with triazole-strobilurin tended to be lower as N increased for STB and were significantly lower for YS. Conversely, under 0 to 70 kg N/ha, GPC decreased when fungicides were used, particularly under the triazole-strobilurin-carboxamide treatment. Cultivars differed with respect to bread-making quality traits. In spite of the increase in GPC with both pathogens, gluten content and bread volume increased with STB but decreased with YS, indicating that the nutritional habit of both pathogens may have a different impact on protein composition. Highlights: Fungicide applications decreased STB and YS without significant differences between fungicide types. The grain protein concentration was increased by STB and YS, whereas fungicides decreased it. Bread volume was modified by fungicide, N and cultivar factors in both, STB and YS experiments. There were differences among wheat cultivars respect to bread-making quality.